The Aircraft Landing Problem - Pelikan, Jan (Communications - Scientific letters of the University of Zilina, 2003)
The problem studied in the paper is an air traffic problem on the airport runway. The goal is finding an aircraft landing sequence that meets the time window for the particular aircraft and at the same time the separation times between two aircraft, which is necessary for the security of landings. The integer programming formulations and the relationship to the traveling salesman problem with cumulative costs are shown.